2008
DOI: 10.1111/j.1365-2222.2008.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐13 induced increases in nitrite levels are primarily driven by increases in inducible nitric oxide synthase as compared with effects on arginases in human primary bronchial epithelial cells

Abstract: These results contrast with many previous results to confirm that Th2 stimuli enhance iNOS expression and activity. While arginase 1 protein decreases in response to IL-13, neither arginase appears to substantially impact nitrite levels in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
111
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(115 citation statements)
references
References 42 publications
2
111
0
2
Order By: Relevance
“…IL-4 and IL-13 induce release of the granulocyte survival factor GMCSF [107] and IL-8 [108] from airway epithelium. IL-4 potentiates IFN-c induced [109], and IL-13 independently induces [110], iNOS production from primary bronchial epithelial cells. IL-4 and IL-13 cause eotaxin release from primary human airway smooth muscle cells (HASM); these responses synergize with IL-1b [111] or TNF-a [112].…”
Section: Inflammationmentioning
confidence: 97%
“…IL-4 and IL-13 induce release of the granulocyte survival factor GMCSF [107] and IL-8 [108] from airway epithelium. IL-4 potentiates IFN-c induced [109], and IL-13 independently induces [110], iNOS production from primary bronchial epithelial cells. IL-4 and IL-13 cause eotaxin release from primary human airway smooth muscle cells (HASM); these responses synergize with IL-1b [111] or TNF-a [112].…”
Section: Inflammationmentioning
confidence: 97%
“…Air-liquid culture of human primary bronchial epithelial cells was performed using Clonetics s B-ALI™ AirLiquid Interface (ALI) medium. The ALI state was maintained for 7-10 days; previous studies have shown this duration is required for mucociliary differentiation [28,29].…”
Section: Preparation Of Epithelial Cellsmentioning
confidence: 99%
“…IL-13 promotes NO-synthase activity and NO production, so elevated FeNO is a good index of TH2 inflammation and high levels of IL-13 in bronchial mucosa [50]. In addition, FeNO can also be used as a predictor of steroid responsiveness more consistently than other parameters.…”
Section: Biomarkersmentioning
confidence: 99%